2020
DOI: 10.1021/acs.joc.0c01791
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Naphthopyrans via Formal (3+3)-Annulation of Propargylic (Aza)-para-Quinone Methides with Naphthols

Abstract: Herein, we report an efficient Brønsted acid-catalyzed formal (3+3)-annulation of (aza)-para-quinone methides generated in situ from propargylic alcohols with naphthol derivatives, which involves a 1,8-conjugate addition/6-endo annulation process. This protocol provides an effective method for preparing important functionalized pyranocoumarins under mild conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 45 publications
1
8
0
Order By: Relevance
“…A Brønsted acid (89) catalyzed synthesis of 2H-chromene derivatives (88), by exploring the reactivity of in situ generated para-quinone methides (90) from propargylic alcohols (86), has been reported by Zhang's group (Scheme 21). [41] While discussing the possible reaction pathways, the authors proposed Scheme 16. Li's approach to chiral chromene derivatives (67).…”
Section: Synthesis Of 2h/4h-chromene and Xanthene Derivativesmentioning
confidence: 99%
“…A Brønsted acid (89) catalyzed synthesis of 2H-chromene derivatives (88), by exploring the reactivity of in situ generated para-quinone methides (90) from propargylic alcohols (86), has been reported by Zhang's group (Scheme 21). [41] While discussing the possible reaction pathways, the authors proposed Scheme 16. Li's approach to chiral chromene derivatives (67).…”
Section: Synthesis Of 2h/4h-chromene and Xanthene Derivativesmentioning
confidence: 99%
“…p -Quinone methides ( p -QMs), as excellent electrophiles, have wide applications in 1,6-additions and annulations. Among them, propargylic p -QMs with alkynyl functional substituents provide a new platform for methodological design since they have both 1,6- and 1,8-electrophilic sites. In 2017, the Sun group realized the first example of asymmetric 1,8-addition of in situ generated propargylic p -QMs to afford chiral tetrasubstituted allenes (Scheme , a) . Then the Li group developed the 1,8-addition of propargylic p -QMs with thiazolones and azlactones .…”
Section: Introductionmentioning
confidence: 99%
“…The Wang group established a cascade 1,8-addition/Diels–Alder reaction for the construction of complex polycyclic compounds (Scheme , b) . Recently, Li and our group developed independently the Brønsted acid catalyzed (3 + 2)- and (3 + 3)-annulations of propargylic p -QMs with indoles and 2-naphthols. These works demonstrated that propargylic p -QMs were useful 3C synthons for the synthesis of five- or six-membered heterocycles (Scheme , c).…”
Section: Introductionmentioning
confidence: 99%
“…Although excellent pioneering work has been achieved, more exploring of propargylic (aza)- p -QMs remains significant, especially in the research field of cycloaddition reactions initiated by 1,8-conjugate addition. In the past few years, our group has been focusing on quinone methide chemistry; the formal (3+3)-annulation of propargylic (aza)- p -QMs with 1,3-dinucleophiles is rare . As shown in Scheme d, we developed an efficient (3+3)-annulation of propargylic (aza)- p -QMs with 4-hydroxy-2 H -chromen-2-one derivatives and 1,3-diketones, affording a synthetic pathway to highly functionalized pyranocoumarin and pyran derivatives.…”
Section: Introductionmentioning
confidence: 99%